loT system for the validation of conditions in shipping couriers - Filipe, P.; Mataloto, B.; Coutinho, C. (2022 IEEE 28th International Conference on Engineering, Technology and Innovation (ICE/ITMC) & 31st International Association For Management of Technology (IAMOT) Joint Conference, 2022)
Online activity has increased over the years and has become a staple in modern society. With it, online shopping businesses have become more common, as well as the number of Internet of Things (loT) devices. As the shopping experience becomes less personal, some people try to exploit the system causing online businesses to increasingly suffer from return frauds. This paper proposes a solution to this problem, integrating loT and image processing. The proposed system uses loT to verify package conditions in courier services, and a database to monitor shipments. To develop the system, a literature review is conducted in order to understand what has been done in the area of logistics services. The literature review is also extended to projects that integrate image processing techniques with loT to determine what tools are used in the development of these projects. Furthermore, the methodology employed for the development of the system is described. This includes the research models, research questions and hypothesis.